Pengembangan Aplikasi Forum Komunitas Lovebird Berbasis Android - Rizal Arianto Indra Cahya; Nurudin Santoso; Faizatul Amalia (Fakultas Ilmu Komputer (FILKOM), Universitas Brawijaya, 2019)
The number of lovebird lovers and breeders along with the development of information technology, many are capturing its beauty through uploading images to social media. But lovers and lovebird breeders still need a system to interact, discuss and search for lovebird information in one place. Mobile applications that have faster and more attractive performance in terms of visuals and users have full access to mobile devices, such as cameras, notifications, speakers, and other features. The simplicity was applied as a forum to help lovers or breeders interact so that the android-based lovebird community forum application was developed. The system was developed by the Rapid Application Development (RAD) method with a needs analysis that produced 27 functional and one non-functional requirements, then implemented using the java programming language. This system has been tested by the white box testing method for unit testing, black box testing for validation testing which produces 27 test cases with 100% results and compatibility testing for non-functional requirements. System compatibility testing can be used with different APIs, namely API 23 with Android version 6.0.1 Marshmallow, API 25 with Android version 7.1.2 Nougat and API 28 with Android version 9 Pie. The test results show that applications can be used in different devices. Compatibility testing uses the SeeTestAutomation tool to get accurate results.